A novel HLA‐C allele, HLA‐C*07:02:01:17N, with an alternative splice site. (24th May 2018) - Shimizu, M.; Kuroda, Y.; Nakajima, F.; Nagai, T.; Satake, M.
Abstract : We describe the identification of alternatively expressed HLA allele C*07:02:01:17N .